2018
DOI: 10.1016/j.molcel.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

The BUB3-BUB1 Complex Promotes Telomere DNA Replication

Abstract: Telomeres and telomere-binding proteins form complex secondary nucleoprotein structures that are critical for genome integrity but can present serious challenges during telomere DNA replication. It remains unclear how telomere replication stress is resolved during S phase. Here, we show that the BUB3-BUB1 complex, a component in spindle assembly checkpoint, binds to telomeres during S phase and promotes telomere DNA replication. Loss of the BUB3-BUB1 complex results in telomere replication defects, including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 89 publications
(139 reference statements)
2
46
0
Order By: Relevance
“…Refining our artificially engineered system to more closely reflect in vivo events, thus allowing continuous cell proliferation, will provide further insight into APB formation and the ALT pathway. BLM protein has been implicated in the ALT pathway as well as telomere replication processes (Sfeir et al 2009;Barefield and Karlseder 2012;Zimmermann et al 2014;Li et al 2018). In the present studies, we demonstrated that BLM helicase is required for the initiation of telomere clustering and telomeric MiDAS through its helicase activity by cooperating with DNA2, which is responsible for the generation of single-stranded telomeric DNAs via long-range resection processes.…”
Section: Discussionsupporting
confidence: 56%
“…Refining our artificially engineered system to more closely reflect in vivo events, thus allowing continuous cell proliferation, will provide further insight into APB formation and the ALT pathway. BLM protein has been implicated in the ALT pathway as well as telomere replication processes (Sfeir et al 2009;Barefield and Karlseder 2012;Zimmermann et al 2014;Li et al 2018). In the present studies, we demonstrated that BLM helicase is required for the initiation of telomere clustering and telomeric MiDAS through its helicase activity by cooperating with DNA2, which is responsible for the generation of single-stranded telomeric DNAs via long-range resection processes.…”
Section: Discussionsupporting
confidence: 56%
“…Bub1-mediated H2ApT120 is sufficient to recruit TOP2A to centromeres and to a non-centromeric chromatin region So far, only a few substrates of Bub1 have been identified, including the anaphase-promoting complex/cyclosome (APC/C) co-activator Cdc20 (Tang et al, 2004;Jia et al, 2016), histone H2A (Kawashima (Li et al, 2018). Among them, histone H2A is the best characterized substrate in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The EMBO Journal 39: e101863 | 2020 ª 2019 The Authors et al, 2010), and the telomere protein TRF1 (Li et al, 2018). Among them, histone H2A is the best characterized substrate in vivo.…”
Section: Bub1 Kinase Activity Is Necessary For Top2a Localization Atmentioning
confidence: 99%
“…Therefore, the replication stress observed in K243R/+ and K243R/+; p53-/- MEFs may be a more direct result of the loss of BubR1 acetylation than from aneuploidy. Interestingly, a recent report showed that Bub1-Bub3, components of the mitotic checkpoint that interact with BubR1, promotes telomere replication in S phase (39). Therefore, there is a possibility that the defect in BubR1 acetylation may have affected the integrity of Bub3-Bub1 in S phase telomere replication fidelity.…”
Section: Discussionmentioning
confidence: 99%